Dependence of the thickness of laminated load-bearing composite panels on the fiber angles - Yu. I. Badrukhin; E. S. Terekhova (Космические аппараты и технологии, 2024)
The designing of thin-walled panels made of laminated composites of minimal weight constrained by strength and buckling is difficult and time-consuming because buckling strongly depends on bending stiffness. This stiffness depends on the percentage of layers and position in layup. The Ration parameters selection algorithm for unsupported and stringer load-bearing panels made of laminated composite with minimal weight and constrained by strength and buckling is presented in this article. The analytical expressions to calculate critical load for unsupported and stringer composite panels under combined loading were obtained to increase the efficiency of the algorithm. Analytical expressions were verified by the finite element method. To validate the calculations, samples of stringer panels with various layups were developed. The samples of stringer panels were tested for buckling. The critical loads realized in tests and obtained by finite element analysis had good coincidence. These results make it possible to use the algorithm to select rational parameters to study the effect of various parameters on the masses of panels made of laminated composite. Layups for an unsupported and stringer panel with fiber angles 0°, ±15°, ±30°, ±45°, ±60°, ±75° and 90° by Ration parameters selection algorithm were obtained in the article.